Representations of "muslim" women in life writing, young adult literature and film in Germany 1990-2015 - Selfe, Lauren (2017)
This thesis investigates representations of “Muslim” women and girls in German popular culture 1990-2015. The thesis offers a symptomatic reading of three under-researched genres in the field: life writing, young adult literature and film. The figure of the “Muslim” woman or girl performs a crucial role in far-reaching socio-political debates in Germany. Indeed, such figures challenge the boundaries of “gender equality” and “secularism” and contest notions of “tolerance” and “integration”. The (in)visibility of “Muslim” women’s bodies and their apparent position in “Islam” function as ostensible indicators of their oppression and of “Islam’s” inherent incompatibility with “western” values. This study analyses the discursive function of such figures in German popular culture via three key research questions: what representational practices surround the figure of the “Muslim” woman or girl in German life writing, young adult literature and film? How do such representations function to produce “non-Muslim” subject positions? What is the function of this figure within narratives of feminism and assertions of “gender equality”? This study understands itself as an intervention into contemporary racist discourses in Germany and operates within a transdisciplinary framework of intersectional feminism, cultural and German studies. Ultimately, this thesis aims to make visible and interrogate the underlying hierarchies and agendas that drive representations of “Muslim” women and girls within the discourses studied.